Comparison of clinicopathological characteristics and long-term survival between patients with gallbladder adenosquamous carcinoma and pure gallbladder adenocarcinoma after curative-intent surgery: a single-center experience in China and a meta-analysis - Lv, Tian-Run; Liu, Fei; Liang, Zuo-Yu; Zou, Rui-Qi; Ma, Wen-Jie; Hu, Hai-Jie; Li, Fu-Yu (Frontiers in Oncology, 2023)
Objective The aim of the study was to evaluate the similarities and differences between gallbladder adenosquamous carcinoma (GBASC) and pure gallbladder adenocarcinoma (GBAC). Methods Patients with GBASC and GBAC from 2010 to 2020 were analyzed in terms of clinicopathological features and long-term survival. Moreover, a meta-analysis was also performed for further validation. Results Our experience: A total of 304 patients with resected GBC were identified, including 34 patients with GBASC and 270 patients with GBAC. Patients with GBASC had a significantly higher preoperative CA199 level (P <0.0001), a significantly higher incidence of liver invasion (P <0.0001), a relatively larger tumor size (P = 0.060), and a significantly higher proportion of patients with T3–4 (P <0.0001) or III–IV disease (P = 0.003). A comparable R0 rate was obtained between two groups (P = 0.328). A significantly worse overall survival (OS) (P = 0.0002) or disease-free survival (DFS) (P = 0.0002) was observed in the GBASC. After propensity score matching, comparable OS (P = 0.9093) and DFS (P = 0.1494) were obtained. Clear margin (P = 0.001), node metastasis (P <0.0001), T stage (P <0.0001), and postoperative adjuvant chemoradiotherapy (P <0.0001) were independent prognostic factors for OS for the entire cohort. Adjuvant chemoradiotherapy had a survival benefit for patients with GBAC, while the survival benefit was still being validated in patients with GBASC. Meta-analysis: With our cohort incorporated, a total of seven studies involving 1,434 patients with GBASC/squamous carcinoma (SC) were identified. GBASC/SC shared a worse prognosis (P <0.00001) and more aggressive tumor biological features than GBAC. Conclusion GBASC/SC shared more aggressive tumor biological features and a much worse prognosis than those with pure GBAC.